Collapse Scenarios of High-Rise Buildings Using Plastic Limit Analysis - G. Liu; D. K. Liu; W. K. Chow (Advances in Civil Engineering)
The Twin Towers of the World Trade Center (WTC) in New York, USA collapsed on 11 September, 2001. The incident is regarded as the most severe disaster for high-rise buildings in history. Investigations into the collapse scenarios are still being conducted. Possible collapse scenarios assessed by local and international experts were reported. Another possible collapse scenario of the WTC based on two hypotheses was proposed in this paper, and the idea of plastic limit analysis was applied to evaluate the approximate limit load. According to the theory analysis and numerical calculations, a conclusion can be drawn that the large fires, aroused by the terrorist attack, play a significant role on the collapse of the WTC.